Epidemiologic case investigation on the zoonotic transmission of Methicillin-resistant Staphylococcus pseudintermedius among dogs and their owners - Luciana Guimarães; Izabel Mello Teixeira; Isabella Thomaz da Silva; Milena Antunes; Camilla Pesset; Carolina Fonseca; Ana Luiza Santos; Marina Farrel Côrtes; Bruno Penna (Elsevier, 2023)
Dogs often carry methicillin-resistant Staphylococci asymptomatically. These bacteria are frequently linked to conditions such as canine pyoderma and otitis. Close interaction between dogs and humans can facilitate the exchange of resistant strains, particularly Methicillin-resistant Staphylococcus pseudintermedius (MRSP). This represents a public health issue, since these strains, in addition to occasionally causing infections in humans, can also serve as a source of resistance and virulence genes for strains of greater importance in human medicine, such as Staphylococcus aureus. Furthermore, MRSP strains are often multidrug resistant, which ends up compromising the treatment of infections. This study aimed to assess the potential transmission of Staphylococcus pseudintermedius among dogs and their owners. We examined a total of one hundred canine samples collected from cases of pyoderma and otitis to detect the presence of staphylococci. Simultaneously, we conducted evaluations on all dog owners. Staphylococci strains were identified using MALDI-TOF MS and PCR targeting the nuc gene. Methicillin resistance screening was also performed by detecting the mecA gene using PCR. Among the sampled dogs, 64 carried S. pseudintermedius. Nine were identified as MRSP. In six instances, dogs and their owners exhibited S. pseudintermedius. These samples underwent genome sequencing and were screened for antimicrobial resistance genes, SCCmec typing, MLST characterization, and Single Nucleotide Polymorphisms (SNP) analyses. The results of the phylogenetic analysis revealed that in three cases, dogs and owners had closely related isolates, suggesting interspecies transmission. Two of these cases involved MRSP and one MSSP. Moreover, in the two MRSP cases, the same SCCmec type (type V) was detected. Additionally, the sequence type was consistent across all three cases involving dogs and owners (MSSP ST2277, MRSP ST2282, and ST2286). These findings strongly indicate a transmission event. Since Staphylococcus pseudintermedius is primarily isolated from canine samples, it is plausible that dogs may have acted as a potential source. In the remaining three cases, despite identifying the same species in both samples, they had notable phylogenetic differences.